Performance indicators of photovoltaic heat-pumps. Issue 10 (October 2019) - Lorenzo, C.; Narvarte, L.
Abstract: In the last few decades, the demand for reversible heating and cooling systems has increased significantly, together with the need to generate energy in a more efficient and sustainable way. Consequently, the concept of solar photovoltaic (PV) powered heat pumps (HP) has become very attractive in order to match the heating/cooling demand with a renewable and environmentally-friendly energy source. This paper presents a review of the different solutions for PV-HP systems that have been studied theoretically and/or experimentally tested, and of the Key Performance Indicators (KPIs) that were mainly used. An analysis of these traditional KPIs has been performed and their boundaries were identified. As a result, new KPIs (PR25, PRref, 25, SPFPV-HP and SPFPV-HP, ref, 25 ) were proposed for trying to mitigate such limitations, as well as for evaluating not only the quality of the HP and the PV system, but also the quality of their integration and the renewable character of the whole PV-HP system. This paper is aimed to be framed in the common effort of the PV-HP research community to reach a set of KPIs that allow comparing the different future works and, therefore, a set of recommendations and future research lines are also proposed. Abstract : Performance indicator; Heat-pump; Photovoltaic/Thermal; photovoltaic; Engineering; Electrical engineering; Energy engineering; Industrial engineering; Systems engineering